Planar Ultra-Wideband (UWB) Antenna with C-Band Rejection Using Self-Complementary Structures - Ojaroudi, Nasser; Ghadimi, Noradin; Ojaroudi, Yasser (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, we describe an application of the Self-Complementary Structures (SCS) to design a low-profile UWB monopole antenna with band-notched function. The proposed antenna consists of a square radiating patch with a rotated Z-shaped slot, a ground plane with a rectangular slot and rotated Z-shaped parasitic structure inside slot; which provides a wide usable fractional bandwidth of more than 125% (2.81- 12.63 GHz), with band-notched function around 3.7-4.2 GHz, to avoid interference from C-band communications. In the presented antenna, by using a rotated Z-shaped parasitic structure inside the rectangular slot in the ground plane, additional resonances are excited and hence much wider impedance bandwidth can be produced; especially at the higher band. To generate a band-stop characteristic, we use the self-complementary structure of the configuration that was inserted in the ground plane, which is a rotated Z-shaped slot at square radiating patch; with this design we can give a C-band rejection performance. The designed antenna has a small dimension of 12×18×0.8 mm3 .